Possibilities for improving the food system at the military academy - economic aspects - Arsić, Slaviša N. (Vojnotehnički glasnik / Military Technical Courier, 2014)
The process of professionalisation of the Serbian Army has caused qualitative and quantitative changes in the personnel structure and has led to the reduction in the numerical strength of its members. The restaurant at the Military Academy has faced infrastructural and organisational ballasts in its capacity for food preparation and distribution thus making the Military Academy food system uneconomic. The capacities of the restaurant are designed to allow for the preparation and distribution of 40% more meals than the actual needs, which, in the economic context, places unnecessary financial burden on the limited amount of funds allocated for this purpose. In terms of economic principles, it is possible to reduce or completely eliminate the negative effects through employing redundant workforce or finding alternative ways to organise the food system at the Military academy in a more rational way. The article represents a "pro et contra" analysis that places an emphasis on some relevant facts in finding expedient solutions. The food system at the Military Academy  was analyzed through the cause-effect relations of the factors within and outside the system and through the efforts to improve the system functioning from organizational, economic, technological and nutrition security aspects, based on current scientific knowledge and domestic and foreign experience. Introduction ”Optimizing food consumption, while meeting the needs of the food with the available resources is one of the vital issues”. Trends in creating a professional, efficient and effective military organizationwith limited resources dictate a need to find and implement better solutions in the defense and in the field of nutrition of the Serbian Army. The importance of nutrition in the functioning of almost all modern armies is priceless, especially at the Military Academy  which generates officers of the Serbian Army. Both internal and external  interest groups,  - those with active participation in the process as well as those  affected by it directly and indirectly - are highly interested in finding an efficient food system implementation model. The modalities of organising food systems at the Military Academy In order to improve the performance of the organisation and to achieve the projected goals, it is necessary to: - analyse the feasibility of preserving the existing capacity, - consider the implementation of other modalities, - implement the chosen mode of nutrition. Feasibility analysis The analysis should be performed taking into account all aspects of internal and external environment, potential opportunities and potential threats, strengths and weaknesses of the organization and their potential impact on stakeholders. The discussion should focus on the fact that the existing human, material and organizational capacities were created with great effort over a long period of time and in better material circumstances. The value of the existing capacities is not fully visible through the prism of material parameters. The essence or "know - how" (to know how to do things the right way) is not seen at first sight , cannot be bought in the market and can be acquired only over the long term through specific tasks in a specific way. Employing a part of unused capacity Some capacity (about 40%) of the Military Academy  restaurant can be hired for the purpose of preparing and distributing food in other organizational units of the Serbian Army with a disproportion (designed/used) in the preparation and distribution of food or for organising the food system for the members the Serbian Army during worktime. In the closer area of the Military Academy  there are two barracks (within  the radius of 1000m) that self-cater and have oversized capacity (about 52%). Combining the food systems of all three  sites for food production and their reliance on the capacities of the Military Academy  (which are the largest and most sophisticated) would provide full employment of the Military Academy  capacities and reduce overall food costs. Implementation of experiences of foreign armies Austria has implemented an army "Cook & Chill" concept, Figure 3, and reduced the number of food preparation by 75%, the number of food distribution points by 34% and the number of personnel by 52%. Annual food costs in the Austrian army in the period before the introduction of this concept were 75 million euros. The benefits achieved by introducing the "Cook & Chill" feeding system are: - Preparation is not time-limited. It is carried out at a time that is most convenient from the aspect of the organization of the process and the availability of raw materials at favorable prices. - Better capacity utilization, which is reflected in minimizing fixed costs per serving. - Connecting locations – food preparation sites. - More economic engagement of the personnel. - The negative consequences are reflected in the reduction of the nutritional properties of food, which is directly related to the consumers’ satisfaction . Namely, due to oxidation and other chemical processes, frozen and subsequently heated food  loses flavor, texture and thermosensitive nutrients. Hiring the "Dedinje" Military Facility as a supplier of preprocessed food for the members of the Military Academy. In the "Dedinje" Military Facility in Belgrade, there are four restaurants, two of which are capable of preparing the required 1000 - 1200 rations: - "Centralni dom Vojske" is excluded as a solution because it rents a  significant part of its capacity during weekends, and a possible expansion of its production capacity is unprofitable. - The Bristol Hotel could expand the existing facilities (there are infrastructural possibilities to adapt a part of the building for food preparation and distribution of meals) and it has a good location, next to the bus station, which is important in terms of the timeliness of food distribution because on the way to the Military Academy  there are no critical points that can hinder traffic flow.. Purchase of food in the market Food can be purchased in the market by signing a contract with a competent company that could meet the defined criteria for the food supply to the members of the Military Academy . The market research was done on 10th  September 2010. The aim of the research - to determine the number of companies in the production and distribution of food whose competence can meet the demands of the food supply system at the Military Academy . The method of research - desk method, based on external resources available on the Internet . The criteria for the selection of these companies are: - competence (the credibility of clients), - size of their production capacity, - character of their  production, - quality of service, - logistic support in the distribution and serving of meals, - range of meals (specific eating habits), - flexibility in the planning of production and distribution of meals, and - timely placement opportunities. The Military Academy  capacity engagemet The capacity could be leased  to competent civilian firms dealing with the preparation and distribution of food. The advantages are reflected in additional food cost reduction opportunities  and in the investment in the upgrade and modernization of the infrastruture in line with the latest trends and requirements of the standards in the preparation and distribution of food. After the expiry of the contract period, modernized facilities would be made available to the Serbian Army. Suggestions for the improvement of the food system at the Military Academy The choice of the optimal solution of nutrition at the Military Academy  should take into account two aspects: - Security, which guarantees continuous, timely and full supply of food for all scenarios (peacetime, military exercises, emergency responses). - Economic, which is reflected in lower costs of mealswhose diet quality is prescribed by the Serbian Army Diet Plan. . Given the fact that the market segment of bidders of preprocessed food that might satisfy a strategic buyer such as the Military Academy is under-developed compared to the needs, and that there are no regulatory requirements to provide a rapid response to a discontinuity in the food supply in case of a disfunction of suppliers, the priority criterion in deciding on the choice of the optimal solution should be security and then the economy and efficiency. Conclusion The main advantage of catering is reflected in the ability to streamline the military costs of food and to focus on improving military skills, while leaving other tasks to more competent subjects outside the defense system. The experiences of the armies from the region indicate that catering in the military of transition countries can generate significant problems, which leads to the cancellation of initial positive effects and increases the cost of food in the long term, over the planned amount.
Keywords: catering; preparation; food; Military